The first political order how sex shapes governance and national security worldwide - Hudson, Valerie M., 1958-; Bowen, Donna Lee, 1947-; Nielsen, Perpetua Lynne (New York Columbia University Press, 2020)
"Global history records an astonishing variety of forms of social organization. Yet almost universally, males subordinate females. How does the relationship between men and women shape the wider political order? The First Political Order is a groundbreaking demonstration that the persistent and systematic subordination of women underlies all other institutions, with wide-ranging implications for global security and development. Incorporating research findings spanning a variety of social science disciplines and comprehensive empirical data detailing the status of women around the globe, the book shows that female subordination functions almost as a curse upon nations. A society's choice to subjugate women has significant negative consequences: worse governance, worse conflict, worse stability, worse economic performance, worse food security, worse health, worse demographic problems, worse environmental protection, and worse social progress. Yet despite the pervasive power of social and political structures that subordinate women, history-and the data-reveal possibilities for progress. The First Political Order shows that when steps are taken to reduce the hold of inequitable laws, customs, and practices, outcomes for all improve. It offers a new paradigm for understanding insecurity, instability, autocracy, and violence, explaining what the international community can do now to promote more equitable relations between men and women and, thereby, security and peace. With comprehensive empirical evidence of the wide-ranging harm of subjugating women, it is an important book for security scholars, social scientists, policy makers, historians, and advocates for women worldwide"--
The First Political Order -- The First Political Order Is the Sexual Political Order -- The Oldest Security Provision Mechanism -- Assessing the Patrilineal/Fraternal Syndrome Today -- The Effects of the First Political Order on Governance and National Security -- The Effects of the Syndrome, Part I: Governance and National Security -- The Tremors Caused by Obstructed Marriage Markets: A Closer Look -- The Effects of the Syndrome, Part II: Human, Economic, and Environmental -- Security -- The Effects by the Numbers: The Syndrome and Measures of National Outcomes -- Change -- Change: Historical Successes and Failures -- Conclusions and Contemporary Applications
Print version record
Includes bibliographical references (pages 561-590) and index
JSTOR
Keywords: Sex discrimination against women -- History; Sex role -- History; Women's rights -- History; Social structure -- History; National security -- History; Discrimination à l'égard des femmes -- Histoire; Rôle selon le sexe -- Histoire; Femmes -- Droits -- Histoire; Structure sociale -- Histoire; POLITICAL SCIENCE -- Security (National & International); POLITICAL SCIENCE -- Political Freedom; National security; Sex discrimination against women; Sex role; Social structure; Women's rights; History